Microstructural and chemical surface and rim zone changes of ferrite‐perlite 42CrMo4 steel after electrochemical machining. Issue 11 (12th November 2021) - Ehle, L.C.; Harst, S.; Meyer, H.; Schupp, A.; Beyss, O.; Rommes, B.; Klink, A.; Schwedt, A.; Zander, D.; Weirich, T.E.; Mayer, J.
Abstract: Electrochemical machining is based on the anodic dissolution of most metals and generates high quality polished surfaces. However, ferrite‐perlite 42CrMo4 steel reveals local optical changes at the surface after electrochemical finishing, such as a widely variable surface finish from shiny (reflective) to rough (dark) surfaces even after one processing step. The optical different surface areas of ferrite‐perlite 42CrMo4 steel (AISI 4140) are studied by different electron microscopy techniques, x‐ray diffraction and x‐ray photoelectron spectroscopy to gain information about the local chemistry of the reaction layers and residual stresses of the rim zone. The results show that the rim zone for the different surface areas are about 50 nm–100 nm thick and contain oxygen. Selected area diffraction reveals the formation of iron(II/III) oxide (Fe3 O4 ) and x‐ray photoelectron spectroscopy confirms the formation of a mixed iron oxide (Fe3‐x O4 ) with a variation of the oxidation state for both near‐surface rim zones. Furthermore, the reflective surfaces reveal a homogeneous dissolution of ferrite and cementite lamellae whereas the rough surfaces show a preferred dissolution of cementite and an inhomogeneous dissolution of ferrite within the rim zone. X‐ray diffraction measurements do not show any introduced residual stresses in the rim zone. Abstract : Investigation of different surface zones (reflective and rough) generated by electrochemical machining of 42CrMo4 steel with sodium nitrate electrolyte. Different characterization methods like energy dispersive spectroscopy, x‐ray photoelectron spectroscopy and selected area diffraction were used to determine the composition of the reaction layer. Translation abstract: Die elektrochemische Bearbeitung basiert auf der anodischen Auflösung der meisten Metalle und erzeugt polierte Oberflächen mit einer hohen Oberflächenqualität. Nichtsdestotrotz weist der ferritisch perlitische 42CrMo4 Stahl eine deutlich unterschiedliche Oberflächenqualität von einer optisch glänzenden bis zu einer dunklen, schwarzen Oberfläche auf. Die optisch unterschiedlichen Oberflächen werden mit verschiedenen elektronenmikroskopischen Methoden, Röntgenbeugung und Röntgenphotonenspektroskopie untersucht, um Informationen über die lokale chemische Zusammensetzung der Reaktionsschichten und die Eigenspannungen an der Oberfläche zu erhalten. Die Ergebnisse zeigen, dass die Randschicht ca. 50 nm–100 nm dick ist und Sauerstoff enthält. Feinbereichsbeugung zeigt die Bildung von Eisen(II/III)‐Oxid, und Röntgenphotonenspektroskopie bestätigt die Bildung verschiedener Eisenoxide mit einer Variation des Oxidationszustandes für beide oberflächennahen Randschichten. Die glänzende Oberfläche zeigt eine homogene Auflösung von Ferrit‐ und Zementitlamellen, wohingegen die dunkle Oberfläche eine bevorzugte Auflösung von Zementitlamellen und eine inhomogene Auflösung von Ferrit aufweist. Röntgenbeugung zeigt keine, durch den Prozess eingebrachte Eigenspannungen in der Randschicht.